Loose Part: Finding Innovation in Learning Early Childhood Education - Rahma Valentina Dewi, Elfrida; Hibana, Hibana; Ali, Musyafa (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to describe and analyze teachers' experience with practicing loose part media innovation in early childhood learning and their implications for child development.Design/methods/approach – This study is qualitative descriptive with phenomenological design. The subject of this study is four teachers at PAUD Wadas Kelir. Data collection processes obtain through in-depth interviews, observations, and documentation, and data analysis processes by reducing, presenting, and verifying data.Findings – The results of this study are that the loose part media innovation carried out by the teachers at PAUD Wadas Kelir includes the selection of loose part materials, motions, learning materials, and song or rhythm. The implication of loose part media in early childhood learning is the achievement of child development aspects, children's fine motor development in the form of coordination, and the ability To make motion simple like the clap. Development of cognitive showed with the child's ability to read and mention letters and numbers. Development of child art showed the ability to coordinate motion with rhythm or song, as well as a creation from loose parts material. Finally, the development of language child showed with the acquisition of new vocabulary and the ability to read the moment or after the play following the writing or the shape that has been compiled.Research implications/limitations – This study only focuses on aspects of loose part media innovation in the learning process and its implications for children’s development, so the limitations of this research are developmental aspects that are not focused on and are less sharp.Practical implications – This study contributes as additional reference material for teachers to develop loose media for children learning.Originality/value – This study gives a deep understanding of the innovation of learning media with loose part materials.Paper type: Research paper